Effects of Integrative Behavioral Couple Therapy on Infertility Self-efficacy, Dyadic Adjustment, and Sexual Satisfaction in Infertile Couples - Fatemeh Vazirnia; Javad Karimi; Kourosh Goodarzi; Masoud Sadeghi (Iran University of Medical Sciences, 2021)
Background: Given the rising rate of infertility, the prevalence of mental health disorders in infertile couples is undeniable. The present study aimed to investigate the effects of Integrative Behavioral Couple Therapy (IBCT) on infertility self-efficacy, dyadic adjustment, and sexual satisfaction in infertile couples.  Methods: The present single-case experimental study used a multiple-baseline design. The statistical population of the study included all infertile couples referring to infertility centers in Ahvaz City, Iran, in 2019. The research instruments included the Infertility Self-Efficacy Scale (ISE), the Dyadic Adjustment Scale (DAS), and the Sexual Satisfaction Questionnaire (SSQ). Following a diagnostic interview, 3 couples were selected using the convenience sampling technique. Integrative behavioral couple therapy was conducted in twelve 120-minute sessions for the intervention group. The second couple entered the study in the second session of the first couple; the third couple enrolled the treatment plan in the third session of the first couple and the second session of the second couple. All questionnaires were completed in the first, third, sixth, eighth, and tenth sessions; the study participants were followed up and re-assessed two months later. The collected data were analyzed in SPSS using chart analysis, reliable change index, and significance statistics. Results: The provided IBCT increased infertility self-efficacy (39.04%), dyadic adjustment (25.91%), and sexual satisfaction (55.01%) in infertile couples. Besides, the improvement lasted throughout the follow-up which indicated the effectiveness of IBCT on infertility self-efficiency, dyadic adjustment, and sexual satisfaction in the study subjects. Conclusion: IBCT can be effective in improving personal and marital variables in infertile couples with infertility problems in addition to their marital problems.